(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article analyzes the technology for producing paper from corn (Zea mays L.), its environmental advantages, and economic prospects. Currently, the widespread use of wood in paper production is reducing forest resources and disrupting the ecological balance. Therefore, the use of fast-growing and regenerative plants as an alternative raw material has become a pressing issue.During the research, cellulose fibers were extracted from corn stalks through chemical treatment (using NaOH and H2O2) to produce high-quality, smooth, and environmentally friendly paper samples. The results showed that corn waste has great potential as a cheap, widespread, and renewable raw material. This technology serves to reduce tree felling, efficiently utilize waste, and ensure environmental sustainability. In the future, producing paper based on corn will be economically beneficial and environmentally friendly.